A covering Ka‐band two‐way switch filter module using a three‐line and an E‐plane waveguide band‐pass filters. Issue 4 (28th October 2014) - Wang, Zhigang; Xu, Ruimin; Yan, Bo
ABSTRACT: A millimeter‐wave ultrawideband two‐way switch filter module is presented in this article. The switch filter module covers whole Ka‐band (26–40 GHz), and is composed of two wideband band‐pass filters and two monolithic microwave integrated circuit (MMIC) single pole two throw (SP2T) switches. One filter is realized using E ‐plane iris waveguide band‐pass filter, and another is realized by a novel 11‐pole three‐line microstrip structure band‐pass filter. Compared with the traditional three‐line filter, the proposed three‐line filter not only retains virtues of the traditional three‐line filter, but also resolves drawbacks of it, which include discontinuities between adjacent sections, many parameters of design, and no effective matching circuits at input/output ports. The developed switch filter module is fabricated using hybrid integrated technology, which has a size of 51 × 26 × 9.8 mm 3, and interconnections between MMICs and microstrip are established by bond wires. The fabricated switch filter module exhibits excellent performances: for two different states, the measured insertion loss and return loss are all better than 7 and 10 dB in each pass‐band, respectively. © 2014 Wiley Periodicals, Inc. Int J RF and Microwave CAE 25:305–310, 2015.